Gestão democrática em um CEI - Centro de Educação Infantil da cidade de São Paulo - Mello, Marcia Curti de (2019)
This study aimed to analyze the effective application of democratic management in a Center for Early Childhood Education (CEI) in the city of São Paulo. Based on the premise that this management model is present in the current legislation and that through its implementation it is possible to guarantee an active participation of the community in the school environment, while knowledge and culture are offered to the population, especially to the population. low, it is considered necessary to evaluate the reality of democratic school management. For this verification, a qualitative exploratory research was carried out through a case study, in the years 2017 and 2018, the collection instrument was a questionnaire that led to the conclusion that there is still a long way to go so that democratic management exists correctly where all involved in decision-making, either on behalf of disinterested managers or teachers, because of lack of community participation, or simply lack of information. Although it was carried out in only one CEI, it was possible to experience the change of managers four times, allowing the analysis of different types of management.The school unit has School Council, Fiscal Council and Parents and Masters Association, the process of school is by public tender. The indicators suggest that the relationship between family, school and society remains distant. As for autonomy, its presence is limited, and even if there is a relationship with participation, the educational system remains rigid and centralizing.